Feminine Da'wah in Counter-Radicalism: Messaging Strategies of Female Clerics in West Java - Fanaqi, Chotijah; Amartiwi, Hendarsita (Tashwirul Afkar, 2023)
This study explores the strategic role of female clerics in the Garut and Tasikmalaya regions in countering religious radicalism through feminine, empathetic, and contextually grounded community da'wah practices. The primary objective is to analyse how feminine da'wah functions as a cultural strategy that not only conveys religious teachings but also constructs a discourse of moderate Islam that is inclusive, dialogical, and gender-just. Employing a qualitative approach within a constructivist paradigm, this research adopts a case study method with data collected through in-depth interviews, participatory observation in female majelis taklim, and documentation of da'wah materials. The findings reveal that the da’iyah (female preachers) employ communication methods based on narrative, open dialogue, and social therapy; and that their da'wah content reinterprets key concepts such as jihad, hijrah, and gendered fiqh through the lenses of justice and community resilience. The study contributes to the development of a grassroots-based counter-radicalism model by highlighting female religious leadership in sacred spaces. It further demonstrates that majelis taklim can serve as safe spaces for ideological recovery, social empowerment, and theological innovation. The originality of this research lies in its integration of healing pedagogy, gender-based transformative Islamic discourse, and local da'wah strategies, offering a novel epistemological contribution to Islamic studies, gender justice, and community resilience against radicalism.